2022
DOI: 10.1155/2022/4187826
|View full text |Cite|
|
Sign up to set email alerts
|

Application of Polypyrrole Cellulose Nanocrystalline Composite Conductive Material in Garment Design

Abstract: The Chinese nation has a long cultural history and has deep attainments in food, clothing, art, and other cultural fields. With the development of science, technology, economy, and culture, new materials continue to appear, providing new ideas for clothing design. Polypyrrole is a common conductive polymer. The pure pyrrole monomer presents a colorless oily liquid at room temperature, slightly soluble in water and nontoxic. Nanocrystals, also called nanoscale crystals, use high-energy polymer spheres to pack c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…According to the data, Cu/Co-hybrid MOF/PVA fiber nanostructures have strength tests of about 16 N/mm 2 . This amount is significant compared to previous polymers (Ngadiman et al, 2015;Su et al, 2022). The strengths of copper-containing MOF nanostructures I), cobaltcontaining MOF nanostructures II), and Cu/Co-hybrid nanostructures III) were obtained as 5.6 N/mm 2 , 1.9 N/mm 2 , and 2.3 N/mm 2 respectively ((n = 3) ± SD).…”
Section: Antibacterial and Antifungal Activitiesmentioning
confidence: 61%
“…According to the data, Cu/Co-hybrid MOF/PVA fiber nanostructures have strength tests of about 16 N/mm 2 . This amount is significant compared to previous polymers (Ngadiman et al, 2015;Su et al, 2022). The strengths of copper-containing MOF nanostructures I), cobaltcontaining MOF nanostructures II), and Cu/Co-hybrid nanostructures III) were obtained as 5.6 N/mm 2 , 1.9 N/mm 2 , and 2.3 N/mm 2 respectively ((n = 3) ± SD).…”
Section: Antibacterial and Antifungal Activitiesmentioning
confidence: 61%
“…Polyvinylpyrrolidone nanofibers 780 0.31 1.17 Frontiers in Chemistry frontiersin.org methanol extract of D. mucronata (15.8 N/mm 2 ) is higher than that of polyvinylpyrrolidone nanofibers (10.8 N/mm 2 ). A lliterature review showed that the synthesized compound has a higher flexural strength than some of the previously synthesized similar compounds (Ngadiman et al, 2015;Su et al, 2022). Figure 5B shows the compressive strength of polyvinylpyrrolidone nanofibers (I) and polyvinylpyrrolidone nanofibers containing methanol extract of D. mucronata (II).…”
Section: The Name Of the Identified Compoundmentioning
confidence: 93%
“…The advantages of a wider application of cellulose-based materials as a new type of absorbents or fillers are related to their abundance, low cost, easy recycling, and biocompatibility. These properties are of special interest for application in different practical fields such as environmental protection [1,2], energy storage [3], garment design [4], surgical pads [5], wound healing [6][7][8], absorbent hygiene products [9], pharmaceuticals [10][11][12], and 3D printing [13]. Cellulose-based gels are also studied as future materials for food packaging and plant agriculture [14], antimicrobial [15], and electroactive [16] materials.…”
Section: Introductionmentioning
confidence: 99%